Big data? qualitative approaches to digital research - Hillyard, Sam; Hand, Martin, 1971- (Studies in qualitative methodology ;, 2014)
This volume seeks to address the emerging relationships between qualitative research and digital data. At the present time, ubiquitous digital data is altering the foci of research, the contexts in which research takes place, and the methods and tools available for qualitative research. Alongside new challenges and opportunities, there are many ways in which established qualitative methods are being used to situate and interpret digital phenomena. This book examines and engages with the ambivalence of digitization, illuminating the diverse ways in which researchers approach, negotiate, understand and interpret objects and practices of digital research. The chapters in this volume are organized around four key themes: researching impacts of digitization on social worlds; researching uses of digital data within social worlds; researching digital visualization of social worlds; researching with digital data and methods. The volume is designed to appeal to qualitative researchers seeking to study processes of digitization, adjust existing methodologies for digital worlds, and develop new ways of examining and using digital research.